Culture of Violence in Local Democracy: Legal Analysis of Bloody Conflicts in Village Head Elections in Bangkalan - Achmad Hariri; Dedy Stansyah (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2025)
The village head election (pilkades) represents a form of local democracy that ideally provides rural communities the means to directly choose their leaders. However, in Bangkalan Regency, pilkades are frequently marred by political conflicts leading to violence and fatalities. This phenomenon presents serious challenges in law enforcement, healthy democratic practices, and the protection of human rights at the local level. This study aims to analyze the dynamics of violent culture within pilkades in Bangkalan and assess the effectiveness of existing regulations in preventing and addressing these conflicts. The socio-legal approach is applied, supported by case studies of violent incidents in pilkades. The discussion focuses on regulatory weaknesses governing pilkades, ineffective law enforcement by the police and judicial institutions, as well as the role of money politics and the lack of government officials' neutrality that exacerbates the situation. Furthermore, this research highlights the influence of local culture, which tends to legitimize violence in political rivalry. The findings reveal that the interaction between strong political influence, personalized campaigns, and local culture creates significant challenges in maintaining electoral integrity. Political actors often resort to intimidation and money politics, increasing the risk of violence. Local governments must collaborate with law enforcement agencies, educate the public, and implement consistent oversight and legal enforcement. In regions like Madura, a culture of violence and patronage intensifies conflicts. A culturally sensitive legal approach, monitoring of violent actors, and community empowerment are critical to fostering peaceful, fair, and democratic elections.